1975
DOI: 10.2466/pms.1975.41.2.403
|View full text |Cite
|
Sign up to set email alerts
|

Blinking and Thinking

Abstract: Blinking is related to certain cognitive processes. For example, individuals “punctuate” their speech by blinking between phrases and at the end of sentences. Daydreaming is associated with low rates of blinking. Blinking occurs between fixations and may be timed so as not to interfere with significant visual input. Apparently, blinking occurs at transitions between internal events and is inhibited at other times. In the experiment reported here, blinking was measured while the activity of operational memory w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

1977
1977
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(59 citation statements)
references
References 10 publications
3
52
0
Order By: Relevance
“…Tasks involving speech or memory increase the blink rate, while those required visual fixation reduce the blink rate (Bentivoglio, Bressman, & Cassetta, 1997;Recarte, Perez, Conchillo, & Nunes, 2008). Daydreaming, which produces visual fixation, is associated with low blink rate (Holland & Tarlow, 1975). Other factors besides cognitive, visual and memory tasks also influence blink rate.…”
Section: Eye Blink Behavior and Detection Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tasks involving speech or memory increase the blink rate, while those required visual fixation reduce the blink rate (Bentivoglio, Bressman, & Cassetta, 1997;Recarte, Perez, Conchillo, & Nunes, 2008). Daydreaming, which produces visual fixation, is associated with low blink rate (Holland & Tarlow, 1975). Other factors besides cognitive, visual and memory tasks also influence blink rate.…”
Section: Eye Blink Behavior and Detection Methodsmentioning
confidence: 99%
“…Although e-Learning session was based on the problem, the stress might be decreased due to the shared responsibility of a group activity. Less cognitive load or low stress, rich critical information or attractive visual information and engage in a computer or visual equipment are some reasons for a low frequency of eye blink (Holland & Tarlow, 1975;Nakano et al, 2009). E-Learners conducted problem based learning in this experiment and it was basically based on the communication among the participants.…”
Section: Wwwccsenetorg/iesmentioning
confidence: 99%
“…Reading is a cognitive process that increases brain activity [16] which leads to longer inter-blink intervals. Another possible explanation for longer intervals is a reflection of the blinking concept as an interlude between ideas or sentences [15]. Figures 7, 8 and 9 show blink rate variability for all subjects during resting sessions and reading, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Studies suggested that blink behaviour during reading is under perceptual and cognitive control [16]. Furthermore, in 1972 Holland and Tarlow [14] not only defined blinking as a function of memory load, "such that the more the items in memory (and presumably the more the rehearsal activity), the fewer the blinks," but also suggested that blinking can be an interlude between ideas or sentences [15]. Researchers have shown the synchronous behaviour in blinking between a listener and a speaker in face-to-face conversation.…”
Section: Introductionmentioning
confidence: 99%
“…Telford and Thompson (1933) determined that spontaneous blink rates vary with the type of mental task. This fmding was extended to include the difficulty of the task (Gregory, 1952;Holland & Tarlow, 1972, 1975Luckiesh, 1944). Typical results show a U-shaped curve across the time course of a single trial which indicates an intermediate-level blink rate during times of no concentration, followed by a depression of blink rates during both the presentation and processing of information, followed by a flurry of eye blinks at the completion of the mental task.…”
mentioning
confidence: 99%